Morfologi Cerita Rakyat Sobey Kororsri (Penerapan Teori Naratologi Vladimir Propp) - Ummu Fatimah Ria Lestari (Kantor Bahasa Provinsi Maluku Utara, 2014)
This research discusses about morphology of Sobey’s folktale Kororsri based on Propp theory. Its problemis how about morphology of Sobey’s folktale Kororsri based on Propp theory. This research used qualitative method. Its data was collected by library research. in its analyzing, the researcher analyzed the morphology of Sobey’s folktale Kororsri by using Propp’s Structural theory. The results of this research the morphology of this folktale consist of: 21 (twenty one) functions, 3 (three) pattern naratology, and 6 (six) speres of actions.